Fire scars, ground vegetation fuels, and prescribed burning : towards better fire management in Fennoscandia - Lindberg, Henrik (Unigrafia, 2021)
Forest fires are an ambivalent issue in Fennoscandia. Although most long-term fire-history studies show a decrease in burned areas, the recent large fires have set challenges for the future given the increasing demand to develop more effective fire management methods. On the other hand, the low impact of fire has raised concerns regarding how to safeguard fire-induced biodiversity. Related to these subjects, in my thesis I have studied fire scar formation, the flammability of the most common ground layer fuels and the state of prescribed burning in Finland. The main findings of my thesis were: 1. Low-intensity forest fires do not necessarily form fire scars in Scots pine stands. The scars found in the study were more common in younger stands as well as in smaller trees and were also formed in higher parts of tree trunks. The variability in shape, size and occurrence of scars suggest that the scar formation in young pine stands may be a stochastic phenomenon depending on fuel load, topography and weather conditions. 2. Prescribed burnings in Finland have declined during recent decades and their current ecological impact is low, despite scientific evidence and expert work having brought about the recommendation to increase burnings. This is primarily explained by the high costs and arduousness of burnings, which have led to decisions in state forest policies and forest certification modifications that have diminished burnings. Combined with low areas burned in wildfires, the current fire regime in Finland can poorly safeguard the fire-dependent habitats and species. 3. The most common ground vegetation fuels in Finnish forests differ in their moisture variation, ignition probability and mass loss during combustion. Amongst studied species reindeer lichen (Cladonia spp.) was clearly the most flammable with the fastest drying rates and the highest ignition probability, whereas fork moss (Dicranum spp.) was the least flammable, while feather moss (Pleurozium schreberi) and stairstep moss (Hylocomium splendens) were ...